PERANCANGAN ALAT PENDETEKSI KEBAKARAN RUMAH MENGGUNAKAN FUZZY LOGIC BERBASIS INTERNET OF THINGS - Istiqlal, Ahmad Zulul (AMMER : JOURNAL OF ACADEMIC & MULTIDICIPLINE RESEARCH; Vol 1 No 01 (2021): September 2021DO - 10.32503/ammer.v1i01.1966, 2021)
Safety in a house is the main thing that must be a concern, the dangers that may occur should be detected as early as possible. Fire-causing factors include electrical short circuits, gas leaks and human error. However, the public is often late to contact and provide information on conditions and location to firefighters, causing the fire to spread further. Therefore, it is necessary to quickly handle fire with fire detection tools using fuzzy logic and internet-based of things, the resulting output of the tool can provide information quickly the state of the house wherever the homeowner is located. The fuzzy input is smoke, fire and temperature and the output is a notification to smartphones and buzzers. there are 3 sensors, namely the MQ-2 sensor, DHT11 sensor, and flame sensor connected to the ESP 32 microcontroller. From the test results, the system can determine various conditions with an accuracy of up to 88.9%. This indicates that the system can work well in determining the condition of the room based on input from the sensor. Keywords : Detection, fire, sensor, smoke, fuzzy